THE EFFECT OF RELIGIUSITY MODERATION ON THE EFFECT OF INCOME ON MUSLIM HOUSEHOLD CONSUMPTION EXPENDITURE - Kusnendi; Bayu Ananda Putra; Aas Nusrasyiah (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
Abstract : Islam regulates one's consumption to stay in the right corridor, such as not wasteful and also pay attention to social values. A good Muslim must be able to distinguish between needs and desires. But today, in reality, there are still many people who live consumptive and hedonism. This study aims to determine the effect of income on Muslim household consumption expenditure and the extent to which religiosity can moderate that influence. The population in this study were housewives in majelis taklim in Sukasari District. The sampling technique is purposive sampling-judgment sampling with a sample size of 97 respondents. The method used in this research is explanatory method with a quantitative approach. Data collection techniques using primary data through interviews and questionnaires to housewives in the Sukasari District taklim assembly. The data analysis technique used is the Moderated Regression Analysis method. The results showed that income significantly affected the consumption expenditure of Muslim households, and the level of religiosity significantly moderated the effect of income on Muslim household consumption expenditure. Keywords: Muslim Household Consumption Expenditure, Income, Religiosity